Audit of enuresis referrals on the waiting list for a tertiary hospital outpatient clinic. (27th May 2021) - Eiselen, Carl; Trajanovska, Misel; Griffith, Andrew; Phan, Tracey; Goldfeld, Sharon; Gibb, Susan; King, Sebastian K
Abstract : Aim: Enuresis, defined as intermittent incontinence occurring exclusively during sleep, affects 4–19% of children, but can be effectively treated using education and alarm‐bell therapies. However, delays in treatment are likely to impact upon the quality of life of the child, parents and carers. Poor quality and incomplete referrals are thought to be a major driver of inefficiencies. The aim of this study was to explore characteristics of enuresis referrals on the waiting list for a general medicine clinic at a tertiary paediatric hospital. Methods: An audit was conducted to examine all enuresis referrals on the general medicine outpatient clinic waiting list in February 2019 at The Royal Children's Hospital, Melbourne. Enuresis referrals with an organic cause and those for children less than 5 years of age were excluded. Results: Of the 2613 referrals on the general medicine waiting list, 486 of 2613 (19%) were related to enuresis. The median age of patients on the waiting list was 8 years and 65% (315/486) were male. Sufficient detail was provided to determine temporal and disease stratification in 45% (218/486) of referrals; primary versus secondary enuresis, and monosymptomatic versus non‐monosymptomatic enuresis. The mean number of days on the waiting list calculated at the time of data extraction (13 February 2019) was 226 (±179) days. Conclusions: The findings from this study suggest that there are long waiting times for enuresis services and referrals often do not contain complete information.